Sliding mode Control using 3D-SVM for Three-phase Four-Leg Shunt Active Filter - Bouzidi Mansour; Benaissa Abdelkader; Barkat Said (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper proposes a sliding mode control strategy for a three-phase shunt active power filter. The SAPF consists of four-leg voltage source inverter bridge. The SAPF ensures full compensation for harmonic phase currents, harmonic neutral current, reactive power compensation and unbalanced nonlinear load currents. The modulation task can be carried out with three dimensional space vector modulation, which operate under a constant switching frequency. The simulation results show that the performance of the four-leg SAPF with the proposed control algorithm – compared with PI controller - is found considerably effective and adequate to compensate harmonics, reactive power, neutral current and balance load currents.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2012